Nick's Tree House - Mendoza, Del; Illustrated by Nagle, Shane (New Delhi Cambridge University Press, 2016)
Bright Sparks Literacy Project is a set of reading materials that provide staged opportunities for children to learn to read in the early years of schooling. Each title draws on a broad base of literacy skills so that teachers can select texts according to students' needs.
Include Color Illustrations